Propuesta de un sistema de riego automatizado eficiente, enfocado a sectores rurales de la provincia de Loja. - Byron David Martínez Lanche, Byron David (2021)
In the present research project, a prototype of automated irrigation was carried out, which has the main advantage of increasing efficiency in the expenditure of water, time and labor, as well as improving crop production and the quality of each one of them. Thorough research in agronomic, hydraulic and programming design was carried out to obtain the necessary knowledge for the technified irrigation system. The corresponding softwares that were used are:  AutoCAD® to make the terrain sketch.  CropWat® that helped to calculate the referential evapotranspiration.  Epanet® to corroborate the hydraulic design calculations and the pressure that will be in each of the sprinklers.  Us Proteus® for the design of the electronic board.  Logo! Soft Comfort® for programming the automated irrigation system.  Arduino® for the programming code of the irrigation prototype. This automated irrigation system helps to monitor the state of the land through an LCD screen, which indicates the humidity of each plot in real time, each zone has its respective humidity sensor, relay and its dependent solenoid valve that through the signal that sends the humidity sensor causes the relay to activate and open its respective solenoid valve. It also has a rain sensor that helps deactivate the pumps and solenoid valves to take advantage of this resource, if the flood ends and the humidity sensor signals that irrigation is not needed, this irrigation system is activated, until reaching the programmed humidity. In addition, it has a manual part for the farmer to fertilize his products according to his convenience. KEY WORDS: Arduino, efficient, corn, irrigation, automated system.